2022
DOI: 10.3171/2021.9.peds21391
|View full text |Cite
|
Sign up to set email alerts
|

Anterior versus posterior entry site for ventriculoperitoneal shunt insertion: a randomized controlled trial by the Hydrocephalus Clinical Research Network

Abstract: OBJECTIVE The primary objective of this trial was to determine if shunt entry site affects the risk of shunt failure. METHODS The authors performed a parallel-design randomized controlled trial with an equal allocation of patients who received shunt placement via the anterior entry site and patients who received shunt placement via the posterior entry site. All patients were children with symptoms or signs of hydrocephalus and ventriculomegaly. Patients were ineligible if they had a prior history of shunt in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The parietal approach was associated with fewer empty holes (N, p = 0.009), frontal & occipital approaches were associated with fewer holes with a scattering of cells ('S', p = 0.023 and 0.029, respectively), and lastly, occipital approach was associated with greater number of holes with protruding tissue aggregates (M, p = 0.041). These results suggest that the entry site of the catheter is a predictor of the degree of shunt obstruction which appears to contradict the overarching outcome of the recent randomized controlled trial through the Hydrocephalus Clinical Research Network 30 . However, this work grouped all types of failure together and did not specify how many of the failed shunts from each approach had failed speci cally due to obstructions.…”
Section: Discussionmentioning
confidence: 76%
“…The parietal approach was associated with fewer empty holes (N, p = 0.009), frontal & occipital approaches were associated with fewer holes with a scattering of cells ('S', p = 0.023 and 0.029, respectively), and lastly, occipital approach was associated with greater number of holes with protruding tissue aggregates (M, p = 0.041). These results suggest that the entry site of the catheter is a predictor of the degree of shunt obstruction which appears to contradict the overarching outcome of the recent randomized controlled trial through the Hydrocephalus Clinical Research Network 30 . However, this work grouped all types of failure together and did not specify how many of the failed shunts from each approach had failed speci cally due to obstructions.…”
Section: Discussionmentioning
confidence: 76%
“…In a child with no seizure after ETV, ventriculoperitoneal shunting was performed 3 weeks after the rst surgery, and epilepsy occurred at 4 years of follow-up, which might be associated with shunt surgery, and a meta-analysis reported that the risk of acquiring seizures/epilepsy in shunted non-infectious hydrocephalus children was 15.75 times higher than that in normal children [18]. A randomized controlled trial compared the anterior and posterior shunt entry sites, and found no signi cant difference in the incidence rate of new-onset epilepsy [19], which could be related to cortical injury and long-term stimulation of the shunt as a foreign body, indicating that cortical disruption or irritation from the shunt catheter itself may contribute to post-shunt seizure development. The child has been well controlled by antiepileptic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited analyses comparing complications and revision rates in relation to the different surgical ventricular access options [10,16,[28][29][30] showing no significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the occurrence of ventricular catheter displacement, we report an overall rate of 4.2% with an even better 2.2% rate considering the cases after the first 50 (initial learning curve). The malpositioning rates reported in the literature vary from 4.5% to 32.5% [11,16,30,31]. We theorize some potential advantages of the temporal access: firstly, the catheter placement does not require the patient's head to be rotated during procedure, as for frontal access, leaving the landmarks fixed and reproducible; secondly, the lateral ventricle can be found as close as 3-4 cm from the cortical surface and a simpler access to the wide area of the ventricular trigone is possible, reducing potential parallax errors and allowing blunt catheter positioning.…”
Section: Discussionmentioning
confidence: 99%